Fermentation of red dragon fruit (Hylocereus polyrhizus) for betalains concentration - Choo, Kah Yee; Kho, Caryn; Ong, Yien Yien; Thoo, Yin Yin; Lim, Lay Hong; Tan, Chin Ping; Ho, Chun Wai (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Red dragon fruits (RDF) contain high levels of health-promoting betalains but its bioavailability in plasma is low (< 1.0%). Therefore, fermentation technique was adopted to improve the yield of betalains presenting in fermented red dragon fruit drink (FRDFD) via concentration. Fermentation of RDF was carried out with autochthonous strains. The objectives of present study were to evaluate 1) the effects of fermentation duration 2) white refined cane sugar to flesh ratio and 3) types of sugar on betalainic (betanin, isobetanin) and non-betalainic phenolic compounds in FRDFD using HPLC-DAD, total phenolic content (TPC) and total flavonoid content (TFC) assay. Results indicated that all fermentation parameters showed a significant effect (p < 0.05) on the yields of betalainic (betanin, isobetanin) and non-betalainic phenolic compounds in FRDFD. The best fermentation parameters were 7 days fermentation at 10% white refined cane sugar to flesh ratio. The highest concentration of betanin, TPC and TFC achieved were 131.68 g/L, 1136.85 mg GAE/100mL and 10.39 mg CE/100mL respectively. The concentration of betanin obtained through best fermentation parameters (131.68 g/L) in present study has increased nine-fold compared to non-optimized fermentation (14.23 g/L). This indicated that fermentation is a potential economic processing technique to concentrate bioactive compounds present in functional drinks.